PENGARUH TEKNIK RELAKSASI BENSON TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI POSBINDU PENYAKITTIDAK MENULAR DESA LINGGAJATI KABUPATEN KUNINGAN - ating Sutanti; Jaenudin; H.Sodikin (Jurnal Kesehatan Mahardika, 2019)
In Kuningan District hypertension patients in puskesmas entered diurutan to 5 patterns of disease all age groups (Profile Kab.Kuningan 2016) .The purpose in this research is to identify the influence of Benson’s Relaxation technique in decreasing the blood pressure of hypertension patiens. This research uses quasi experimental design with one group pretest-posttest design model. The sample technique in this study used total sampling which amounted to 32 respondents, research instrument using aneroid spyghmomanometer and stethoscope, data collection using observation. Data analysis using Normality test and paired sample t test. Research location at at integrated coaching post for non-communicable diseases in Linggajati Village, Kuningan District in June-July 2018. The results showed that the mean systolic blood pressure before and after the Benson relaxation technique was 163,12mmHgbecome 150,47 mmHg, mean diastolic blood pressure before and after relaxation technique Benson was93,28 mmHgbecome 87.19mmHg. The mean systolic blood pressure fell 12.66 mmHg and the diastolic blood pressure was 6.09 mmHg. Value p value 0,000. The conclusion of this research isthe influence of Benson’s Relaxation technique in decreasing the blood pressure of hypertension patiens at integrated coaching post for non-communicable diseases in Linggajati Village, Kuningan District with significance p value 0,000 (<0,005). For people with hypertension is expected to use Benson relaxation techniques to maintain blood pressure stability so as to reduce the use of pharmacological therapy.